Kesediaan Membayar Produk Sayuran Organik di Pasar Modern Jakarta Selatan - Aufanada, Vickitra; Ekowati, T.; Prastiwi, W. D. (AGRARIS: Journal of Agribusiness and Rural Development Research, 2017)
Organic vegetable products tend to have higher prices compare to non organic, therefore most consumers think organic vegetable products are expensive products. This research aims to determine consumers’ willingness to pay (WTP) for organic vegetable product and influencing factors towards WTP. This research was conducted in 6 modern market in South Jakarta by interviewing 100 consumers who were selected using quota sampling technique. Data were analyzed using contingent valuation method (CVM) to determine the average value of consumers’ WTP and logistic regression employed to determine the factors that influence WTP. The results showed that 82% consumers are willing to pay higher prices to buy organic vegetables products, with additional range between 8.5% to 15% from the real price. Factors that significantly influenced consumers’ willingness to pay were education level, monthly income and product quality.